the effect of brand equity and UGC on purchasing decisions that have an impact on the repurchased Intention of MSME superior products in Pasuruan Regency: the effect of brand equity and UGC on purchasing decisions that have an impact on the repurchased Intention of MSME superior products in Pasuruan Regency - Hasanah, Uswatun; Miftahul Huda (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2023)
Increasingly intense business competition through content requires MSME actors to keep abreast of existing technological developments. Therefore, this study was conducted to analyze the effect of brand equity and UGC (user generated content) on purchasing decisions and their impact on repurchase intention. This type of explanatory research with a quantitative approach can be seen how the relationship between brand equity and UGC variables as independent variables with purchase and repurchase decisions intention as the dependent variable. With a population of 116 SME consumer respondents, the superior products of Pasuruan Regency. By collecting data through a questionnaire that was analyzed using SPSS 22. The results of this study partially brand equity and UGC have a positive and significant effect on purchasing decisions, partially brand equity and UGC have a positive and significant effect on repurchase intention, purchasing decisions have a significant positive effect on repurchase intention, and partially brand equity and UGC through purchasing decisions have no effect on repurchase intention